211k views
4 votes
The average rate of change of f from 2 to 3

User Lauris
by
5.7k points

1 Answer

6 votes

For a function of
f, the average rate of change can be found as follows:



ARC=(f(x_(2))-f(x_(1)))/(x_(2)-x_(1))


So, this problem asks for the Average Rate of Change of
f from
x_(1)=2 to
x_(2)=3. In this way, we need to find
f(x_(1)) \ and \ f(x_(2)). As you can see above, we have the graph of
f(x), so we can find these values. Thus, from the graph:



f(x_(1))=4 \\ f(x_(2))=1


Therefore:



ARC=(1-4)/(3-2) \\ \\ \therefore \boxed{ARC=-3}

User Samoka
by
5.8k points